Weakest Bus Identification Based on Modal Analysis and Singular Value Decomposition Techniques - Jalboub, M. K.; Rajamani, H. S.; Abd-Alhameed, R.A.; Ihbal, A. M. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
Voltage instability problems in power system is an important issue that should be taken into consideration during the planning and operation stages of modern power system networks. The system operators always need to know when and where the voltage stability problem can occur in order to apply suitable action to avoid unexpected results. In this paper, a study has been conducted to identify the weakest bus in the power system based on multi-variable control, modal analysis, and Singular Value Decomposition (SVD) techniques for both static and dynamic voltage stability analysis. A typical IEEE 3- machine, 9-bus test power system is used to validate these techniques, for which the test results are presented and discussed.